English language instructors’ assessment beliefs and practices in the Malaysian tertiary context - Elshawa, Niveen R. M (2016)
Language assessment can be a valuable tool for giving information regarding language teaching. Given the importance of assessment that has undergone much change, there are important issues that warrant investigation, particularly those related to language instructors. The main objectives of the study were to investigate the English language instructors’ beliefs about assessment, the assessment practices that English language instructors use in assessing students’ work and the extent to which language instructors' assessment beliefs correspond to their practices. Differences in the assessment beliefs/practices of the English language instructors in terms of TESL qualifications, years of work experience, number of courses taught per week and source of prior assessment training were also investigated.This study employed an explanatory sequential quantitative driven design. In this design, the researcher collected data through two questionnaires and a semistructured interview from six Malaysian universities’ instructors using a purposive sampling strategy. English language instructors were selected as informative and useful subjects for the study based on two criteria: those who are employed full time, and those who are teaching proficiency courses. Using descriptive statistics, the researcher was able to answer the first two questions of the study. Frequency, percentage, means, and standard deviation (SD) were used to report descriptive data. Pearson correlation coefficient was employed to explore the relation between English language instructors’ assessment beliefs and their reported practices. Independent-Samples t-test was used to examine the differences that occurred in the independent variables of the study for the first four hypotheses in both the fourth and the fifth questions of the study, namely: TESL qualification, years of teaching experience, work load and class size. Three one-Way analysis of variance (ANOVA) was employed to examine the differences that occurred among the three groups of the fifth independent variable namely: assessment training.Analysis of data showed that English language instructors believed that the purpose of assessment was to improve teaching and learning. They tended to use a variety of assessment methods to assess students’ language ability in their classrooms giving more weightage on formative assessment (course work) than on summative assessment (final test). Further, they apply process-oriented approach to second language assessment more than product-oriented approach. In addition, they use different types of assessments for every language skill taught in the language unit/center. All correlations between subscales on both assessment beliefs and practices were estimated as positive and statistically significant indicating that instructors’ assessment practices were notably dependent on their assessment beliefs. Finally, this study has found out that none of the hypothesized factors influencing assessment beliefs and practices of English language instructors (TESL qualifications, years of work experience, number of courses taught per week and source of prior assessment training) had any significant difference between different categories of teachers depending on those factors.These findings highlight that instructors should be more empowered in their role as the assessors of students. Their knowledge about what, how, when to assess should be developed through long profession development courses; one-shot workshops or seminars would not be enough to improve instructors’ assessment literacy.